Indonesian Migrant Workers in Japan within the Human Security Framework - Mayumi, Keisha Septi; Argenti, Gili (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2026)
The migration of Indonesian migrant workers to Japan has increased significantly in recent years, driven by Japan's labor shortages resulting from demographic decline and an aging society. Although often framed as a mutually beneficial economic cooperation, this migration also generates various vulnerabilities for Indonesian migrant workers in the destination country. This study aims to analyze the migration of Indonesian migrant workers to Japan within the human security framework. The findings indicate that Indonesian migrant workers in Japan face multidimensional threats, particularly in terms of personal security, economic security, and health security. Therefore, the human security approach provides a more comprehensive perspective by positioning migrant workers as the primary referent of security